HLA-A*11 and novel associations in Malays and Chinese with systemic lupus erythematosus - Mohd-Yusuf, Y.; Phipps, M.E.; Chow, S.K.; Yeap, S.S. (Elsevier, 2011)
We investigated the association of the HLA genes in Malaysian patients with systemic lupus erythematosus (SLE) and their associations with the clinical manifestations in 160 SLE patients (99 Chinese and 61 Malays) and 107 healthy control individuals (58 Chinese and 49 Malays) were studied. Sequence specific primer amplification (PCR-SSP) phototyping techniques were used to analyse 25 HLA-A allele groups, 31 HLA-DR allele groups and 9 HLA-DQ allele groups. Appreciable increases in allele frequencies of HLA-A*11, DRB1*0701, DRB1*1601–1606, DRB5*01–02 and DQB1*05, and decrease in HLA-DRB1*1101–1121, 1411, DRB1*1201–3, DRB1*1301–22, DRB3*0101, 0201, 0202, 0203, 0301 and DQB1*0301, 1304 in SLE patients compared with healthy control individuals. However, after Bonferroni correction (pc < 0.05) only HLA-A*1101, 1102, DRB5*01–02, DQB1*05, DRB1*1201–3, DRB3*0101, 0201, 0202, 0203, 0301 and DQB1*0301, 0304 remained significant. Allele frequencies of DRB1*0701 and DRB4*0101101, 0102, 0103, DQB1*05, DRB1*1301–22, DRB3*0101, 0201, 0202, 0203, 0301 and DQB1*0301, 0304 were significantly increased in Malay SLE patients compared with healthy control individuals. In contrast, Chinese SLE patients had increased allele frequencies of DRB1*1601–1606, DQB1*05, DRB1*1201–3, DRB3*0101, 0201, 0202, 0203, 0301, DRB3*0101, 0201, 0202, 0203, 0301 and DQB1*0301, 0304 compared with healthy control individuals. HLA-A*6801–02 and DRB1*1601–1606 frequencies appeared elevated in a subset of patients with serositis and DRB1* 0401–1122 frequency was elevated in those displaying neurologic disorder. However, unequivocal evidence of these associations would require investigation of substantially larger cohorts. On the whole, our findings suggest that HLA allele associations with SLE are race specific in Malays and Chinese.